Epoxyeicosatrienoic acid analog attenuates angiotensin II hypertension and kidney injury - Hye Khan, Md. Abdul; Falck, John R.; Manthati, Vijaya L.; Campbell, William B.; Imig, John D. (Frontiers in Pharmacology, 2014)
Epoxyeicosatrienoic acids (EETs) contribute to blood pressure regulation leading to the concept that EETs can be therapeutically targeted for hypertension and the associated end organ damage. In the present study, we investigated anti-hypertensive and kidney protective actions of an EET analog, EET-B in angiotensin II (ANG II)-induced hypertension. EET-B was administered in drinking water for 14 days (10 mg/kg/d) and resulted in a decreased blood pressure elevation in ANG II hypertension. At the end of the two-week period, blood pressure was 30 mmHg lower in EET analog-treated ANG II hypertensive rats. The vasodilation of mesenteric resistance arteries to acetylcholine was impaired in ANG II hypertension; however, it was improved with EET-B treatment. Further, EET-B protected the kidney in ANG II hypertension as evidenced by a marked 90% decrease in albuminuria and 54% decrease in nephrinuria. Kidney histology demonstrated a decrease in renal tubular cast formation in EET analog-treated hypertensive rats. In ANG II hypertension, EET-B treatment markedly lowered renal inflammation. Urinary monocyte chemoattractant protein-1 excretion was decreased by 55% and kidney macrophage infiltration was reduced by 52% with EET-B treatment. Overall, our results demonstrate that EET-B has anti-hypertensive properties, improves vascular function, and decreases renal inflammation and injury in ANG II hypertension.